Surgical results of coronary artery bypass grafting without cardiopulmonary bypass: analysis of 3,410 patients - Lima,Ricardo de Carvalho (2003)
OBJECTIVES: Over the past few years, great strides have been made in off-pump coronary surgery. This progress is due to a combination of the advances in surgical techniques and the development of instruments that make it possible to perform this procedure in the most varied situations. This is a retrospective study, the purpose of which is to assess our experience with this procedure over the last eleven and a half years. The authors underscore the rapid progress of the method in recent years and report on its indications, contraindications and results. METHODS: In the period from August 1991 to December 2003, 3,410 consecutively patients suffering from angina pectoris were submitted to off-pump coronary surgery. Ages ranged from 13 to 93 years, with a mean of 63 ± 12.0 years. Males accounted for 58% of the cases. The angina was rated according to the criteria of the Canadian Cardiovascular Society, 6.1% of the patients being in Class I, 6.8% in Class II, 46.3% in Class III and 40.8% in Class IV. RESULTS: Intraoperative mortality was low (0.4%). Hospital mortality (30 postoperative days) was 2.5%. Mortality and morbidity among the octogenarian patients were extremely low compared with patients operated on with cardiopulmonary bypass (CPB) (2.2% versus 12.6%) (p<0.001). Postoperative complications regarded as nonfatal occurred in 7.6%. In the final year no difference was observed between the number of conduits in the patients operated on with and without CPB [with CPB 2.8 ± 1.2 and without 2.8 ± 0.8 (NS)]. Acute myocardial infarction was the most frequent complication, occurring in 2.7% of the patients. The mean time in the intensive care unit was 22.3 hours. CONCLUSIONS: Off-pump coronary surgery, employed as a revascularization technique in patients requiring multiple grafts, is a reproducible procedure, the results of which are similar to those obtained from conventional surgery with CPB. In the present series it was possible to perform coronary artery bypass grafting without CPB in 95% of the patients, thus making all patients with indication for grafting potential candidates for the procedure without CPB.